2021
DOI: 10.1093/cvr/cvab164
|View full text |Cite
|
Sign up to set email alerts
|

Plasma high-density lipoprotein cholesterol and risk of dementia: observational and genetic studies

Abstract: Aims The association of plasma high-density lipoprotein (HDL) cholesterol with risk of dementia is unclear. We therefore tested the hypothesis that high levels of plasma HDL cholesterol are associated with increased risk of dementia and whether a potential association is of a causal nature. Methods and results In two prospective population-based studies, the Copenhagen General Population Study and the Copenhagen City Heart St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…For example, evidence from a cross-sectional study conducted on 1889 Chinese participants reported an inverse U-shaped association between total cholesterol levels and cognitive score only in the subgroup of patients characterized by normal levels of homocysteine [ 325 ], while Huang et al could reach statistical significance only in late-life obese APOE-ε 4 non-carriers [ 326 ]. Furthermore, similar to the U-shaped relationship observed for total cholesterol, higher plasma HDL levels have been found in AD patients versus controls in two prospective population-based investigations [ 327 ], while very low circulating HDL content was reported to be associated with cognitive decline [ 328 ]. Given the central role of apolipoprotein E in the pathogenesis of AD [ 329 ], biomarkers based on its alteration should be investigated.…”
Section: Resultsmentioning
confidence: 64%
“…For example, evidence from a cross-sectional study conducted on 1889 Chinese participants reported an inverse U-shaped association between total cholesterol levels and cognitive score only in the subgroup of patients characterized by normal levels of homocysteine [ 325 ], while Huang et al could reach statistical significance only in late-life obese APOE-ε 4 non-carriers [ 326 ]. Furthermore, similar to the U-shaped relationship observed for total cholesterol, higher plasma HDL levels have been found in AD patients versus controls in two prospective population-based investigations [ 327 ], while very low circulating HDL content was reported to be associated with cognitive decline [ 328 ]. Given the central role of apolipoprotein E in the pathogenesis of AD [ 329 ], biomarkers based on its alteration should be investigated.…”
Section: Resultsmentioning
confidence: 64%
“…Evidence suggests that high total cholesterol levels in mid-life increased the risk of AD in later life [6]. Moreover, high plasma HDL cholesterol has been observationally associated with an increased risk of dementia and AD [8]. However, a study with 19 years of follow-up found that HDL cholesterol levels in mid-life are inversely associated with MCI and dementia in late life [7].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding midlife, hearing loss appears to be the most influential factor, accounting for 8% of the dementia modifiable risk, followed by traumatic brain injury (3%), hypertension (2%), alcohol (1%) and obesity (1%) [3,4]. Not included among those factors, but probably important as well, may be the presence of hypercholesterolemia [5][6][7][8][9] and the exposure to heavy metals or to certain mycotoxins, produced by molds or cyanobacteria [10,11]. Finally, smoking (5% of the total modifiable dementia risk), depression (4%), social isolation (4%), physical inactivity (2%), air pollution (2%) and diabetes (1%) may contribute to an increased risk of dementia at later life.…”
Section: Introductionmentioning
confidence: 99%
“…There were three primary MR studies each for type 2 diabetes [16][17][18] and LDL cholesterol [19][20][21] ; two studies each for HDL cholesterol 19,22 , total cholesterol 19,23 , triglycerides 19,21 , and systolic blood pressure 20,24 ; and one study each for diastolic blood pressure 25 , BMI 26 and circulating glucose 27 (Figure 1). The MR studies for diastolic blood pressure, BMI, and circulating glucose reported an overall estimate produced through the meta-analysis of two or more outcome cohorts.…”
Section: Identification Of Primary Mr Studiesmentioning
confidence: 99%